Skin-To-Skin Care and Breastfeeding in the Perioperative Suite. Issue 2 (March 2015) - Burke-Aaronson, Amanda Claire
Abstract : Abstract: Current trends are moving toward immediate skin-to-skin care after birth of a newborn. This is shown to be highly beneficial, both physiologically and emotionally, to the mother and the baby. Strategies and considerations for initiating skin-to-skin care in the perioperative suite immediately after cesarean birth, such as thermoregulation of the baby in the operative suite, equipment, baby and family positioning, and maternal monitoring, are presented. Initiating skin-to-skin care as soon as possible after birth is recommended. Abstract : Skin-to-skin care immediately after cesarean birth is possible with planning and teamwork.